The dynamic behavior investigation of electric power wheelchair during the obstacle avoidance - Ibrahim, Mohammad Sollehudin; Peeie, M. H. (Institute of Physics Publishing, 2020)
The increment of the People with Disabilities (PWDs) keep increasing in each year and an urge of assisting these PWDs is demanding. Commercial manual wheelchair eases the mobility of the PWDs but there is side effect for the manual wheelchair users that is pain on shoulder area due to extensive daily propulsion of manual wheelchair for mobility. Therefore, this paper presents an approach towards the autonomous wheelchair whereas concerning the PWDs that have disabilities from upper to lower limbs. These paper investigates the dynamic behavior of the autonomous wheelchair during the obstacle avoidance. The experiment conducted on the Electric Power Wheelchair (EPW) and several participants divided base on gender and age for this particular investigation. This experiment uses the EPW as a first step before taking next step towards self-navigation system in order to understand the behavior of the autonomous wheelchair by using the intervention of human input on EPW. The participants will maneuver the EPW via joystick with several speed justifications that is determined during the pre-experimental set-up. This study focused on the changes in speed of both left and right tires and yaw angle during the obstacle avoidance. The data will be used as a reference for the autonomous wheelchair during the obstacle avoidance. The data that maneuvered manually by the participants also serve as the human-machine relationship whereas the data will be interpreted into the control systems that will be developed for the autonomous wheelchair. Based on the results, the changes of velocity could be seen from both left and right tires during the obstacle avoidance base on gender is different but the trend of the results significantly same for both male and female. © Published under licence by IOP Publishing Ltd.